Foreword (to Issue 1) - Gault, T M (Victoria University of Wellington Law Review, 2001)
This article serves as the foreword to this special issue of the Victoria University of Wellington Law Review dedicated to intellectual property law. Gault J (as he was then) states that New Zealand’s intellectual property law has only been subject to academic analysis in recent years, and stresses the need for change and development.